Electroacupuncture versus Escitalopram for mild to moderate Post-Stroke Depression: A randomized non-inferiority trial - Ma, Feixiang; Cao, Guiping; Lu, Lu; Zhu, Yingling; Li, Wanlang; Chen, Li (Frontiers in Psychiatry, 2024)
Objective To explore the efficacy of electroacupuncture in treating post-stroke depression (PSD) by modulating the inflammatory response pathway. Methods One hundred and fifty participants with mild or moderate PSD were randomly divided into 75 cases each in the electroacupuncture group (EA group) and escitalopram group (ESC group). In the EA group, 30 sessions of electroacupuncture were performed on the Baihui (GV 20), Yintang (GV 29), and the ipsilateral Taichong (LR 3) and Hegu (LI 4), simultaneous oral placebo for 40 days. The ESC group received oral escitalopram oxalate tablets 10mg to 20mg for 40 days, plus 30 sessions of sham electroacupuncture. The effectiveness of the treatment was evaluated by the Hamilton Depression Scale (HAMD-17), Self-Depression Scale (SDS), Modified Barthel Index Score (MBI), and the serum levels of IL-1β, IL-6, IL-10, TNF-α, and INF-γ. Results There was no statistically significant difference in the baseline data, HAMD-17, SDS, MBI scores, and serum IL-1β, IL-6, IL-10, TNF-α, and INF-γ levels between the two groups of participants before the intervention (P >0.05). After treatment, HAMD-17 and SDS scores continued to decrease and MBI scores continued to increase in both groups. The differences were statistically significant at the 6th week and baseline, the 10th week and baseline, and the 10th week and the 6th week (all P <0.001). The differences in HAMD-17, SDS, and MBI scores between the two groups at the 6th week were not statistically significant (P=0.110, 0.115, 0.516, respectively); HAMD-17 scores and SDS scores in the EA group were lower than those in the ESC group at the 10th week, and the differences were statistically significant (P=0.002,0.026, respectively). In the 6th week, the serum levels of pro-inflammatory factors such as IL-1β, IL-6, TNF-α, and INF-γ were significantly lower in both groups compared with the baseline, while the level of anti-inflammatory factor IL-10 was significantly higher. The difference between the pre-and post-intervention intra-group comparisons was statistically significant (P <0.001), and the difference between the inter-group comparisons was not statistically significant (P >0.05). No serious adverse events occurred throughout the trial. Both therapies could safely and effectively improve HAMD-17, SDS, and MBI scores and modulate neuroinflammatory responses in PSD participants. After the treatment was stopped, some parameters were better in the EA group than the ESC group in a short time. Conclusion Electroacupuncture is an effective, alternative to escitalopram for the treatment of mild-to-moderate PSD. Clinical trial registration Chinese Clinical Trial Registry (ChiCTR2300072576).